Hubungan Kadar Vitamin D pada Ibu Hamil dengan Berat Bayi Lahir di Kabupaten Tanah Datar dan Kabupaten Solok - Nidya Ikha Putri; Nur Indrawaty Lipoeto; Rauza Sukma Rita; Arif Sabta Aji (Universitas Batanghari Jambi, 2019)
The main cause of infant mortality is Low Birth Weight (LBW). Basd on data obtained from the West Sumatra Provincial Health Office in 2015, from 1376 case of 92.444 babies weighed, and there were 2,066 (2.2%) LBW in 2014. Growth and development of the fetus need vitamin D for cell and bone growth.The design of this study is cross sectional and conducted in Tanah Datar District in the working area of Puskesmas Simabur, Puskesmas Lima Kaum I, and in Puskesmas Lima Kaum II and Solok District in the working area of Puskesmas Talang, Puskesmas Gaek Jua and Puskesmas Tanjung Bingkung from January 2017 to March 2018. The study population was third trimester pregnant women with a population of 60 respondents, by multistage random sampling. Examination of vitamin D levels by ELISA method. Data were analyzed by univariate and bivariate with normality test.The result of this study that level are the average vitamin D content of 25.44 ± 10.49 pg / ml and the median weight of the baby born is 3000 gram. There was a positive relationship between vitamin D levels in pregnant women with birth weight (r = 0,463), (p < 0,05).The conclusion of this research is that there is a significant association between vitamin D levels in pregnant women with infants born weight in West Sumatra.